Respuesta :

Space

Answer:

(f o g)(5) = -13

General Formulas and Concepts:

Pre-Alg

  • Order of Operations: BPEMDAS

Algebra I

  • Composition of functions

Step-by-step explanation:

Step 1: Define

f(x) = 3x - 4

g(x) = -2x + 7

(f o g)(5) is f(g(5))

Step 2: Find composite function

  1. Substitute:                     (f o g)(x) = 3(-2x + 7) - 4
  2. Distribute:                      (f o g)(x) = -6x + 21 - 4
  3. Combine like terms:     (f o g)(x) = -6x + 17

Step 3: Solve

  1. Substitute:                    (f o g)(5) = -6(5) + 17
  2. Multiply:                        (f o g)(5) = -30 + 17
  3. Add:                              (f o g)(5) = -13